Effect of interannual variation in winter vertical mixing on CH4 dynamics in a subtropical reservoir. Issue 7 (22nd July 2015) - Itoh, Masayuki; Kobayashi, Yuki; Chen, Tzong‐Yueh; Tokida, Takeshi; Fukui, Manabu; Kojima, Hisaya; Miki, Takeshi; Tayasu, Ichiro; Shiah, Fuh‐Kwo; Okuda, Noboru
Abstract Although freshwaters are considered to be substantial natural sources of atmospheric methane (CH4), in situ processes of CH4 production and consumption in freshwater ecosystems are poorly understood, especially in subtropical areas, leading to uncertainties in the estimation of global CH4 emissions. To improve our understanding of physical and biogeochemical factors affecting CH4 dynamics in subtropical lakes, we examined vertical and seasonal profiles of dissolved CH4 and its carbon isotope ratio (δ13C) and conducted incubation experiments to assess CH4 production and oxidation in the deep subtropical Fei‐Tsui Reservoir (FTR; Taiwan). The mixing pattern of the FTR is essentially monomixis, but the intensity of winter vertical mixing changes with climatic conditions. In years with incomplete vertical mixing (does not reach the bottom) and subsequent strong thermal stratification resulting in profundal hypoxia, we observed increases in sedimentary CH4 production and thus profundal CH4 storage with the development of reducing conditions. In contrast, in years with strong winter vertical mixing to the bottom of the reservoir, CH4 production was suppressed under NO3−‐rich conditions, during which denitrifiers have the competitive advantage over methanogens. Diffusive emission from profundal CH4 storage appeared to be negligible due to the efficiency of CH4 oxidation during ascent through methane‐oxidizing bacteria (MOB) activity. Most of the profundal CH4 was rapidly oxidized by MOB in both oxic and anoxic layers, as characterized by its carbon isotope signature. In contrast, aerobic CH4 production in the subsurface layer, which may be enhanced under high temperatures in summer, may account for a large portion of atmospheric CH4 emissions from this reservoir. Our CH4 profiling results provide valuable information for future studies predicting CH4 emissions from subtropical lakes with the progress of global warming.